2022
DOI: 10.3390/biom12070975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gum Acacia on the Intestinal Bioavailability of n-3 Polyunsaturated Fatty Acids in Rats

Abstract: Lipid emulsification is a technique that is being explored for improving the bioavailability of omega 3 (n-3) long chain (LC) fatty acid (FA). The nature of the emulsifiers can differently impact the lipid bioavailability via a modification of the lipolysis step. Among natural emulsifiers, gum acacia (GA), an indigestible polysaccharide, provides protective encapsulation of n-3 by forming a specifically crown-like shape around lipid drops, which could also impact the digestion step. Despite the interest in lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 72 publications
(119 reference statements)
0
12
0
Order By: Relevance
“…In an animal study, rats could easily absorb ALA from the ingested PUFA oil powder‐supplemented diet and had significantly increased plasma ALA and EPA (Kaushik et al., 2015; Yoshikiyo et al., 2019). Another study on rats proved encapsulated omega‐3 PUFA oil showed bioavailability 2.5–3 times more than the bulk oil when assessed by the total FA concentration in the lymph (Couëdelo et al., 2022). The wall materials protect PUFA not only against environmental pro‐oxidants but also against the breakdown or destruction of omega‐3 PUFA by GI conditions like low pH and gastric enzymes before it reaches the small intestine for digestion, thus leading to controlled release and retention of functionality (Hu et al., 2021).…”
Section: Bioavailability Of Omega‐3 Fatty Acidmentioning
confidence: 99%
See 4 more Smart Citations
“…In an animal study, rats could easily absorb ALA from the ingested PUFA oil powder‐supplemented diet and had significantly increased plasma ALA and EPA (Kaushik et al., 2015; Yoshikiyo et al., 2019). Another study on rats proved encapsulated omega‐3 PUFA oil showed bioavailability 2.5–3 times more than the bulk oil when assessed by the total FA concentration in the lymph (Couëdelo et al., 2022). The wall materials protect PUFA not only against environmental pro‐oxidants but also against the breakdown or destruction of omega‐3 PUFA by GI conditions like low pH and gastric enzymes before it reaches the small intestine for digestion, thus leading to controlled release and retention of functionality (Hu et al., 2021).…”
Section: Bioavailability Of Omega‐3 Fatty Acidmentioning
confidence: 99%
“…Emulsifiers have varying effects on lipid digestion because their characteristic surface activity alters the enzyme activity and rate of lipolysis (Lamothe et al., 2020; McClements et al., 2016). Casein and Tween (Tween 20 and Tween 80) slow down lipolysis and decrease the bioavailability of FA, but lecithin increases FA bioavailability by favoring the digestion step at its initiation (Couëdelo et al., 2022; Li et al., 2020; Sehl et al., 2020). The lipase cannot bind to the surface of the oil droplet because Tween's intersurface action is greater than that of the lipase (Li et al., 2020).…”
Section: Bioavailability Of Omega‐3 Fatty Acidmentioning
confidence: 99%
See 3 more Smart Citations